BUILDING AN INTEGRAL APPROACH IN COMBATING SEXUAL VIOLENCE CRIMES - Andi Khadafi (Green Publisher, 2023)
This study aims to determine the penal policy in overcoming the current criminal act of sexual violence and to build an integral approach in the future of sexual violence in the legislation. The problem of this research is about how the policy of dealing with criminal acts of sexual violence is currently and in the future. The research method used is normative juridical. The conclusion of this research is to build an integral approach in overcoming the crime of sexual violence in the future by way of material criminal law, criminal law and the implementation of criminal law now integrally by using legal comparisons to various countries, especially concerning all aspects and values ??that exist in Indonesia. community related to the prevention of criminal acts of sexual violence.